THE BENEFITS AND OUTCOMES OF ROLEPLAY AS A CBME EDUCATIONAL TOOL IN UNDERSTANDING THE CONCEPTS OF PHARMACOLOGY AMONG SECOND YEAR MBBS STUDENTS IN A TEACHING HOSPITAL: A PROSPECTIVE CROSSSECTIONAL QUESTIONNAIRE BASED STUDY. - Hemanth G.V; Siva Sushma A; Sreelakshmi G; Anitha Alivelu; Subhash babu P (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Many studies were conducted among MBBS students to assess the implementation of new competency-based medical education (CBME) curriculum. Studies assessing the Roleplay implemented by CBME as an educational tool in Pharmacology theory classes are limited. Aim and Objectives: The aim of this study was to assess the benefits and outcomes of Roleplay in understanding the concepts in Pharmacology among II year MBBS students in Government medical college, Kadapa. Materials and Methods: In a six weeks period every pharmacology theory class is taught to the II MBBS students by traditional lecture method along with roleplay at the last ten minutes of one hour theory class. Few students were invited to perform Roleplay with prior practice regarding the concerned theory topic. After six weeks, a  questionnaire was shared through whatsapp to 2nd MBBS students through Google Forms containing ten questions by using likert scale. The students were allowed to answer them and submit. The data was analyzed using Microsoft Excel sheet by SPSS software.  Results: In four point Likert scale we got an average mean score of “ 3.85 ” showing that above 97% 0f the students were in the opinion that the that Roleplay as an educational tool was good and reached to them in a right way. Conclusion: From the students’ perspective, the role-play concept was very much appreciated and was considered to be an effective means for learning communication skills.